Top-down HPLC-ESI–MS proteomic analysis of saliva of edentulous subjects evidenced high levels of cystatin A, cystatin B and SPRR3. (May 2017) - Manconi, Barbara; Liori, Barbara; Cabras, Tiziana; Iavarone, Federica; Manni, Armando; Messana, Irene; Castagnola, Massimo; Olianas, Alessandra
Highlights: The acidic soluble fraction of whole saliva from 11 edentulous subjects and 11 dentate control subjects was analyzed by top-down RP-HPLC- ESI–MS. Levels of cystatin A, S-derivatives of cystatin B and S-glutathionylated SPRR3 were higher in edentulous subjects with respect to dentate controls. Cystatin A, cystatins B and SPRR3 are major constituent of the cornified cell envelope. Abstract: Objective: This study aims to analyze the salivary peptidome/proteome of edentulous subject with respect to dentate control subjects. Design: Unstimulated whole saliva, collected from 11 edentulous subjects (age 60–76 years) and 11 dentate age-matched control subjects, was immediately treated with 0.2% aqueous trifluoroacetic acid and the acidic soluble fraction analyzed by High Performace Liquid Chromatography-Mass Spectrometry. The relative abundance of the salivary peptides/proteins was determined by measuring the area of the High Performace Liquid Chromatography-Mass Spectrometry eXtracted Ion Current peaks which is linearly proportional to peptide/protein concentration under identical experimental conditions. Levels of salivary peptides/proteins in the two groups were compared by the nonparametric Mann-Whitney test to evidence statistically significant differences. Results: Levels of cystatin A, S-glutathionylated, S-cystenylated, S-S dimer derivatives of cystatin B and S-glutathionylated derivative of SPRR3, were found significantly higher in edentulous subjects with respect to dentate controls. The major peptides and proteins typically deriving from salivary glands did not show any statistically significant differences. Conclusions: Cystatin A, S-glutathionylated, S-cystenylated, S-S dimer derivatives of cystatin B and S-glutathionylated derivative of SPRR3, which are mainly of intracellular origin and represent the major constituents of the cornified cell envelope are a clue of inflammation of mucosal epithelia.